Comparing the most demanding passages of official matches and training drills in elite roller hockey - Fernández, D.; Novelles, A.; Tarragó, R.; Reche, X. (Apunts Educación Física y Deportes, 2018)
The aim of this research was to identify and compare the most demanding passages (MDP) in elite roller hockey in competition and in different training situations. Data were collected using WIMU PRO™ sensors with inertial micro-technology and ultra-wide band positioning. Eight professional roller hockey players from the Spanish First Division League (Ok Liga) were analysed during the 2017-2018 season. The MDP were studied using a rolling average method in which maximal values were calculated for three different time windows (1`, 2` and 5`) in official matches and in four different training drills commonly used in the weekly team-training schedule: practice match (TRAINING MATCH), 4 vs. 4 in half court and one transition (4vs4+1T), 4 vs. 4 in half court and two transitions (4vs4+2T) and 3 vs. 2 wave transition drill (3vs2). The variable used for the comparison was the distance covered in high speed skating (HSS: >18 km/h; m·min) and only the maximum value of each player, drill and time window were stored for the study. The results show that training drills could not reproduce the maximum conditional effort that occurs in an official match in any time window. Moreover, all the situations and games analysed had higher levels of effort as the time of the window studied decreased. The analysis of shorter time windows could be a topic for future research. In conclusion, the findings of this study pave the way for future research into the identification and comparison of the most demanding scenarios in elite roller hockey that may help coaches to design training situations.